Pengaruh Pembelajaran Kooperatif Tipe Think Pair Share (TPS) terhadap Kemampuan Pemecahan Masalah Matematis Siswa Kelas VIII SMP YLPI Perhentian Marpoyan: The Effect of Cooperative Learning Type Think Pair Share (TPS) on Mathematical Problem Solving Ability of Class VIII Students of SMP YLPI Perhentian Marpoyan - Azura Fitri; Lilis Marina Angraini (Journal of Research in Science and Mathematics Education (J-RSME), 2023)
Objective: This study aims to determine whether or not there is an effect of Think Pair Share (TPS) cooperative learning model on mathematical problem-solving ability of seventh grade students of YLPI Perhentian Marpoyan Junior High School. Methodology: This research is an experimental research. The sampling technique used random sampling. The population of this study was 29 students of class VIII YLPI Perhentian Marpoyan Junior High School and the sample of this study was class VIII-2 as the experimental class and class VIII-1 as the control class. The data collection instrument used was the mathematical problem-solving ability test. Data analysis techniques used are descriptive statistical data analysis and inferential statistical data analysis. Findings: Based on the results of the t-test calculation obtained  t hitung = 4,55 with α=0,05 and db=27 Obtained t tabel = 2,051. Significance: Hence, it can be concluded that the null hypothesis is rejected and the alternative hypothesis is accepted, which means that there is an effect of the Think Pair Share (TPS) type cooperative learning model on the mathematical problem-solving ability of VIII-grade students of YLPI Perhentian Marpoyan Junior High School.